The Potential of ACTH in the Genesis of Primary Aldosteronism - Funder, John W. (Frontiers in Endocrinology, 2016)
Aldosterone is a homeostatic hormone, rising in volume depletion, sodium deficiency and potassium loading, in response to angiotensin11 and elevation of plasma potassium. Pathophysiologically, in primary aldosteronism (PA) aldosterone levels are inappropriate for the patient’s sodium and potassium status, and thus outside the normal feedback loop. ACTH is equivalent with A11 and [K+] in elevating aldosterone: its effects differ from those of the other secretagogues in four ways. First, it is not sustained; second, it raises aldosterone and cortisol secretion with equal potency; third it is outside the normal feedback loops, reflecting the epithelial action of aldosterone; and finally its possible role in driving inappropriate aldosterone secretion (aka Primary Aldosteronism) is not widely recognised. Thirty years ago it was shown that on a fixed sodium intake of 175meq/d 36 of 100 unselected hypertensives, in whom PA has been excluded on contemporary criteria, had 24 hour urinary aldosterone levels above the upper limit of normotensive controls. More recently, the dexamethasone enhanced fludrocortisone suppression test (FDST) showed 29% of unselected hypertensives to have plasma aldosterone concentrations above the upper limit of normotensive controls. In subjects negative for PA on the FDST, 27% were extremely hyper-responsive to ultra-low dose ACTH infusion; the remaining 73% showed minimal aldosterone elevation, as did normotensive controls: all three groups had negligible cortisol responses. On treadmill testing no differences were found between groups in (minimally altered) ACTH and cortisol levels: hyper-responders to ultra-low ACTH, however showed a major elevation in plasma aldosterone concentration. The implications of these studies,